Effect of Processing and Partial Substitution of Baobab Seed Meal on Commercial Ross Broilers’ Growth Performance - Pauline Matambo; Tinotenda Nhovoro; Rumbidzai Blessing Nhara; Faith Matiza Ruzengwe; Tinoziva Hungwe; Prosper Bright Muvhuringi; Jameson Madzana; Tendai Mujati; Ngavaite Chigede (Research in Agriculture Livestock and Fisheries, 2025)
The increasing global population and climate-related challenges have intensified the search for alternative, non-competing protein sources to replace conventional feed proteins. This study evaluated the effects of partially substituting roasted soybean meal with baobab seed meal on growth performance and carcass characteristics of commercial Ross broiler chickens in Tongwe, Ward 4, Beitbridge District, Zimbabwe. A completely randomized design (CRD) was used with two iso-nitrogenous dietary treatments, each replicated six times with eight birds per replicate. Sorghum served as the primary energy source, while soybean and baobab seed meals provided protein. Sorghum was ash-treated to reduce tannins, soybeans were roasted to inactivate trypsin inhibitors, and baobab seeds were boiled for one hour to reduce tannins and phytates. Feed formulation was carried out using FeedSoft software to achieve crude protein levels of 20% in grower and 18% in finisher diets. After six weeks, no significant differences (p = 0.7) were observed in live body weight between treatments. Meat taste and carcass color parameters also showed no notable differences. The study concludes that partial replacement of soybean meal with baobab seed meal during the finisher phase is feasible without compromising broiler growth performance, meat quality, or carcass color. Further research is recommended to assess the protein quality and optimal inclusion levels of baobab seed meal. Res. Agric. Livest. Fish. Vol. 12, No. 3, December 2025: 455-464